2020
DOI: 10.1002/term.3030
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical strain improves artificial equine tendon constructs in vitro

Abstract: Tendon injuries are a common cause of morbidity in humans. They also occur frequently in horses, and the horse provides a relevant, large animal model in which to test novel therapies. To develop novel cell therapies that can aid tendon regeneration and reduce subsequent reinjury rates, the mechanisms that control tendon tissue regeneration and matrix remodelling need to be better understood. Although a range of chemical cues have been explored (growth factors, media etc.), the influence of the mechanical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…To further improve cell distribution and induce mechanotransduction, cyclic uniaxial strain was applied. The frequency of the cyclic strain was with 1 Hz lower than the stride frequency found in equine canter, which is approximately 2 Hz, but comparable to the strain used by other studies, in particular for the promotion of stem cell differentiation towards tenocytes [31][32][33]. While some studies applied strain for as little as 15 to 20 min per 24 h, as 15 min per 24 h were sufficient for a notable effect regarding mechanical induction, longer application periods were suggested [33,34].…”
Section: Discussionsupporting
confidence: 63%
“…To further improve cell distribution and induce mechanotransduction, cyclic uniaxial strain was applied. The frequency of the cyclic strain was with 1 Hz lower than the stride frequency found in equine canter, which is approximately 2 Hz, but comparable to the strain used by other studies, in particular for the promotion of stem cell differentiation towards tenocytes [31][32][33]. While some studies applied strain for as little as 15 to 20 min per 24 h, as 15 min per 24 h were sufficient for a notable effect regarding mechanical induction, longer application periods were suggested [33,34].…”
Section: Discussionsupporting
confidence: 63%
“…The design for the frames includes two internal tendon attachment points which avoid the use of grips or clamps to secure the ends of the tissue and were optimised to distribute the mechanical stress through the tissue without breaking the fibrin hydrogel scaffold. 38,45 After 14 days culture in six-well plates, the cell-seeded fibrin hydrogels formed tendon-like tissues between the attachment points which were easily removed from the well plate and slotted into individual wells of the bioreactor chamber. At this stage, two 90° adapter arms were attached (Figure 2(b)) to connected points A and B of the frame to the corresponding points on the bioreactor chamber and six-way tensile arm (Figure 2(d)).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers use either custom-made tensile bioreactors or commercially available systems such as the EBERS TC-3 and the CellScale MC series. Our search of literature published between January 2016 and April 2020 indicates that of 24 published studies on cyclic loading in tendon tissue engineering, three groups published data generated using a CellScale bioreactor 25 , 28 , 34 and one group published using an EBERS TC-3 bioreactor, 41 with the remaining 20 using custom-designed bioreactors 19 24 , 26 , 27 , 29 33 , 35 40 , 42 , 43 (summarised in Table 1 ). There is a clear requirement for greater reproducibility and consistency in the methodological approach to enable both comparative research and translation towards effective clinical therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal for physiological mimicking is, therefore, the application of intermittent cyclic loading ( Cao et al, 2006 ; Scott et al, 2011 ). Different studies show favorable cell characteristics (elongation, metabolic activity, gene levels and protein production) administering intermittent cyclic strain, while a negative influence of continuous cyclic strain is frequently reported ( Cao et al, 2006 ; Riboh et al, 2008 ; Bosworth et al, 2014 ; Youngstrom et al, 2015 ; Atkinson et al, 2020 ). For example, Riboh et al (2008) compared the application of constant versus intermittent cyclic strain in a 2D, Flexcell Strain Unit (Flexcell International; Hillsborough, NC, United States).…”
Section: Advanced: Incorporating Bioreactorsmentioning
confidence: 99%
“… Wu et al (2017) cultured three different cell types (tenocytes, AT-MSCs and HUVECs) on synthetic electrospun fibers (PCL/PLA scaffolds) and stated that dynamic culture in a custom-made mechanical stimulation device promoted collagen production and tenogenic differentiation ( Wu et al, 2017 ). Atkinson et al (2020) demonstrated with the use of a custom-designed bioreactor that equine tendon constructs within collagen I gels, analogous to other species, show improved mechanics when exposed to cyclic strain ( Atkinson et al, 2020 ).…”
Section: Advanced: Incorporating Bioreactorsmentioning
confidence: 99%